Trace metal distribution in the sediment cores of mangrove ecosystems along northern Kerala coast, south-west coast of India. (April 2020) - Manju, M.N.; Ratheesh Kumar, C.S.; Resmi, P.; Gireeshkumar, T.R.; Joseph, Manju Mary; Salas, P.M.; Chandramohanakumar, N.
Abstract: Core sediment samples were collected from five mangrove ecosystems along northern Kerala coast (Kunjimangalam: S1, Pazhayangadi: S2, Pappinissery: S3, Thalassery: S4, and Kadalundi: S5) to assess the status of heavy metal pollution. S1 recorded comparatively lower metal concentration at surface (except Pb) due to low organic content and sandy texture, while the reverse was true for S3. Higher metal contents were recorded at S5 (0–5 cm), which was attributed to its unique biogeochemical behavior. Enrichment factor and geoaccumulation index indicated moderate enrichment for Cd, and the pollution load index revealed progressive deterioration of sediment quality at S5 (0–5 cm). There was no harmful effect of trace metals on biological community (except Ni) according to Sediment Quality Guidelines. Major processes controlling trace metal accumulation in these systems are diagenetic processes, precipitation of heavy metals as sulfides, and the presence of Fe, Mn-oxy hydroxides, which act as adsorption sites for other metals. Highlights: Core sediment samples were collected from mangrove ecosystems along northern Kerala coast. Heavy metal accumulation is enhanced by the fine sediment granulometry and enriched organic carbon content. Most of the metals are associated with Fe hydroxides. Formation of metal sulphides is controlling the dispersal of Cu, Ni and Zn. According to Sediment Quality Guidelines, Ni can cause harmful effects on biological community.